PENINGKATAN KESADARAN KESEHATAN KERJA MELALUI SOSIALISASI INTERAKTIF PADA BURUH TALI KARET LIMBAH BAN MOTOR - Lutfiyah, Lutfiyah; Sulisawati, Dwi Noviani; Murtinasari, Frida; Hidayatin, Nur (INCIDENTAL : Journal Of Community Service and Empowerment, 2025)
This community service activity aims to increase awareness of Occupational Health and Safety (OHS) among rubber cord workers who process motorcycle tire waste in Sukorejo Village, Bangsalsari Subdistrict, Jember Regency. This home-based industry poses high occupational risks, such as exposure to tire dust, fine particles, hazardous chemicals, and the potential for injuries from sharp tools. Low understanding and use of Personal Protective Equipment (PPE) exacerbate the risks of respiratory issues, skin irritation, and cuts. The method used was an interactive 3-hour session, including lectures, participatory discussions, and demonstrations on proper PPE usage. Evaluation results showed a significant increase in workers' knowledge about specific workplace risks and the importance of PPE. Additionally, the workers demonstrated strong motivation to adopt safer, healthier, and more productive work practices on an ongoing basis. The impact of this activity is expected to reduce workplace accidents and work-related illnesses while enhancing productivity in the rubber rope processing home industry. Future recommendations include regular mentoring and the provision of affordable PPE to ensure the sustainability of OSH practices in the field.